أثر الإبداع التكنولوجي على تنافسية المؤسسة الاقتصادية دراسة حالة مؤسسة موبيليس: The impact of technological innovation on the competitiveness of the economic enterprise, a case study of the Mobilis Corporation - يوسف لحسن; وهيبة سراج (Journal of North African Economies, 2025)
This study aims to determine the impact of technological innovation on the competitiveness of the economic enterprise. We have chosen the Mobilis Corporation to conduct a case study. Spss to process it, as 59 questionnaires were distributed and we obtained only 40 of them that were valid for analysis. The results of the study showed that there is a direct relationship between technological innovation and competitiveness, and that the institution under study adopts technological innovation to resist fierce competition in its sector of activity, which is witnessing continuous global development.